Uncertainties Arising During Drilling And Performance Of Flight Auger - Cast Piles - F. M. Abdrabbo (Deep Foundations Institute, 1993)
Flight auger bored piles are formed by screwing a continuous flight auger into the ground, and pumping cement/sand grout or concrete down the hollow stem of the auger as its withdrawn. The auger is driven at the top by hydraulic or electrical motor and is guided by a vertical crane leader. Loading tests on concrete piles are described. The stability plot method is used to drive the shaft friction and the end bearing load components of the pile capacity. This paper outlines features of crucial construction factors that affect the geotechnical capacity of this type of piles. These factors include, vertical speed of auger during boring, grout factor, grout pressure, number of reborings, type of material, and slump of concrete used to form the piles. Two of these factors are highlighted in this paper. It was found that, shaft resistance is independent of grout factor, whilst point resistance increases as grout factor increases. Nevertheless the engineer should decide the safe pile load associated with the most economical grout factor. High vertical speed of auger during boring of piles may cause disaster for the adjacent buildings, due to soil decompression.